ChemInform Abstract: Palladium‐Catalyzed Cyclization of Bromoenynamides to Tricyclic Azacycles: Synthesis of Trikentrin‐Like Frameworks. Issue 43 (21st October 2014) - Campbell, Craig D.; Greenaway, Rebecca L.; Holton, Oliver T.; Chapman, Helen A.; Anderson, Edward A.
Abstract Cascade reaction of bromoenynamides such as (I) and (V) equipped with an additional alkyne or ynamide substituent affords azatricyclic products (II) and (VI), respectively.